Report on an invasive pest, the fall armyworm Spodoptera frugiperda (J. E. Smith) (Lepidoptera : Noctuidae) on maize cultivation in Bintulu, Sarawak - Muhamad Azmi Mohammed,; Ameyra Aman-Zuki,; Wan Asrina Wan Yahaya, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The fall armyworm (FAW), Spodoptera frugiperda is a polyphagous pest for the family of Poaceae crops such as maize, sugarcane, sorghum, and rice by feeding on the leaves, stems, and reproductive plant’s parts. Natives from America, this invasive pest has been reported to spread rapidly to Europe, Africa, India, and Sri Lanka. Currently, this pest was reported in the Southeast Asia region, such as Myanmar, Thailand, and Indonesia. In this study, an occurrence of FAW infesting maize cultivation in Bintulu, Sarawak were reported. This pest species was identified by its larval morphological features such as an inverted “Y” shape on the head and four dotted black spots arranged in a square shape on their 8th abdominal segment. The FAW larvae were found as early as the vegetative growth stage 3 (V3) and continue up to the reproductive phase 1 (R1) of the crop. The damages of FAW are serious on the shoots and bore the stalk causing the crop to stunt and died. The larvae were also causing economic injuries to the farmers by feeding on the newly formed cobs. This study served as an early report on FAW infestation on maize in East Malaysia from mid-2019. The immediate and proper monitoring and management of this pest could prevent further damages to other crops in Malaysia.